Pengembangan Media Interaktif Berbasis Lectora Inspire Pada Mata Pelajaran PAI Di SMP Negeri 1 Ujas Mas - M. Iqbal Liayong Pratama; Nina Sulvia Ayuna Sari; Hamengkubuwono Hamengkubuwono (Journal on Education, 2023)
The objective of creating this interactive media is to facilitate and simplify the process of delivering educational content for teachers while making it engaging, enjoyable, and easily understandable for students. The interactive media is developed using the lectora inspire software application. By utilizing this application, the interactive media presents captivating material that can guide students towards independent learning. The research follows the research and development approach with the implementation of a 4D development model. Data collection for this project will involve various methods such as observation, interviews, and questionnaires. The results from the testing of the media demonstrate that the program's features perform effectively and have been verified with satisfactory outcomes